PELAKSANAAN PENGELOLAAN DAN PEMANTAUAN LINGKUNGAN BERDASARKAN DOKUMEN RKL & RPL SERTA CORPORATE SOCIAL RESPONSIBILITY (CSR) DI PT. TAMAN NUSA GIANYAR - Tri Sumandiarta, I Komang; Ardhana, IPG; Mahendra, Made Sudiana (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2016)
Taman Budaya Nusantara is one of the tourism site that is located in Gianyar which being managed by PT. Taman Nusa. The negative impact from tourism site is an enhancement of environmental destruction. This research aims to analyze the adherence implementation of the Environmental Management Plan document (RKL), Environmental Monitoring Plan document (RPL) and the implementation of CSR Program. The methods that used were in the research are case approachment (The Case Approach), Legislation approachment (The Statue Approach), and Conceptual approachment (Analytical and ConcePT. ual Approach). The result of the research shows that PT. Taman Nusa did not comply to the terms of legislation according to the implementation of EIA document five aspects, is Permitting, Water Pollution Control, Air Pollution Control, Hazardoces Waste Management and Solid Waste Management. PT. Taman Nusa has fulfilled obligations in carrying out its social responsibility, economic and environment by actualizing the CSR program according to the Article 74 of Constitution No 40 of 2007 about Limited Liability Company (PT). The implementation of CSR program covers 14% of the total Sidan village. PT. Taman Nusa Should perform a reparation in managing and controlling the environment according to the rules of constitution which have been suggested by local government through the BLH Gianyar to do some evaluation and reviewing the AMDAL Document of PT. Taman Nusa and conductlinkagemappingof stakeholder sandterritoriesforthe implementation of theoverallCSRprogramin the VillageSidan.
Keywords: Environmental Impact Analysis (EIA); Environmental Management Plan (RKL); Environmental Monitoring Plan (RPL); CSR Program